WEERKAATSENDE WOORDE: ’N (OUTO)BIOGRAFIESE REFLEKSIE VAN ’N (PRAKTIESE) TEOLOOG - Van den Berg, J. A. (Scriptura, 2020)
This article discloses, in an intimate personal manner and based on an (auto)biographical journey, some of the secrets and treasures of a (practical) theological academic author. Drawing on an initial casual contact with a practical theologian’s personal living-space, it presents a trajectory for charting the development of academic writing. Unexpected milestones along the path of documented practical theological research include aspects of a local, concrete and embodied description. Each of these milestones describes the steep elevation and gradient along the course. In viewing these milestones, one discovers that both writer and reader share in the most personal matters and that this intimacy has general significance. An analysis of the reflecting words of a (practical) theologian reveals potential coordinates for future writing and charting of other personal theological academic secrets and disclosures.